Wellbeing in high-performance swimming: A grounded theory study - Uzzell, K. S.; Knight, C. J.; Pankow, K.; Hill, D. M. (Psychology of Sport and Exercise, 2024)
The demands of elite sport have the potential to negatively impact on athletes` wellbeing (e.g., Arnold & Fletcher, 2012; Rice et al., 2016). Despite this, not all elite athletes experience detrimental effects, rather some individuals thrive in an elite sports environment. The reasons why some athletes experience positive wellbeing while others struggle remains unclear although, in part, due to methodological limitations of previous research. To overcome these limitations, the purpose of the current study was to examine how change in high-performance swimmers` wellbeing occurs. Grounded theory methodology was used to enable examination of processes of change. Semi-structured interviews with 22 current and five retired swimmers, eight coaches, and seven support staff were used to generate data alongside observations and field notes. The resultant theory illustrated how a dominant performance narrative influenced the development and maintenance of an exclusive swimmer identity that was tied to performance. Specifically, transitions were highlighted as critical points where wellbeing was likely to be affected, due to the increased potential for change and uncertainty to impact on performance and subsequently identity. However, the use of proactive coping strategies, such as anticipating and planning, as well as accessing and utilising appropriate support were shown to help minimise the impact on wellbeing.